Peningkatan Peran Olahraga Sepeda MTB pada Kontribusi Pelestarian Hutan Ngaduman Merbabu Mediator ISSI Kota Salatiga - Subono, Agung; Ariyanto, Shodiq Eko (Muria Jurnal Layanan Masyarakat, 2023)
After the Covid-19 pandemic, people became aware of improving health and preserving the environment. This community service aims to increase the role of sports of MTB (Mountain Bike) in contributing to forest conservation in Ngaduman Village, Merbabu Mountains by involving ISSI Salatiga City as a moderator. ISSI (Ikatan Sepeda Sport Indonesia) is a Regional Institution for Bicycle Racing in Indonesia, which is in charge of governance standards for cyclists on a Mountain. ISSI is also a member of UCI and ACC, namely international bicycle racing events that can bring in tourism and increase regional income. The results of community service show the importance of publication facilities for Mount Merbabu tourism and MTB bicycle racing events; management of tourism, officials, and MTB bicycle tracks (tracks); and the importance of coordinating with the Office of the Ministry of Youth and Sport and KONI - ISSI of Salatiga City and related parties such as the local community and Perhutani.